CHARACTERISTICS OF THE QUR'ᾹNIC MANUSCRIPT OF SYEIKH SURAU TANJUANG - Idris, Mhd.; Marlina, Inda (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2021)
This study aims to determine the characteristics of the Qur'ānic manuscripts of Syeikh Surau Tanjuang and it’s differences from the Qur'ān rasm usmaniy. This research is a library research with a philological and codicological approach. The primary source of this research is the Qur'ānic manuscripts of Syeikh Surau Tanjuang and the secondary sources used are books that are directly related to the discussion. The results of this study indicate that three manuscripts of the Qur'ān were found as relics of Syeikh Surau Tanjuang. The manuscripts were collected by Hayatun Nufus and Datuak Trans as the Tanjuang tribe. The characteristics of the Qur'ānic manuscripts of Syeikh Surau Tanjuang generally do not have a cover and are written in naskhi script. The condition is quite apprehensive because it is no longer intact, many pages are missing, the paper is torn, even eaten by termites, and the paper has started to turn yellow. The comparison of the Qur'ān Syeikh Surau Tanjuang manuscripts with the Qur'ān rasm utsmani can be seen from several aspects, including the aspect of rasm, punctuation (syakl), tajwid sign, waqaf sign which in general has clear differences. Besides that, there were also some errors in writing.